2006
DOI: 10.1037/0894-4105.20.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging of working memory in schizophrenia: Task performance as a moderating variable.

Abstract: Functional neuroimaging studies in schizophrenia have demonstrated abnormal activation of dorsolateral prefrontal cortex (DLPFC) during working memory (WM) performance. However, findings of increased and decreased activity have been reported. The authors used meta-analysis to investigate whether diverging results arise as a function of differential WM task performance between patients and control participants. Results indicate that the magnitude of the group difference in WM performance is a moderator of DLPFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 59 publications
8
116
0
3
Order By: Relevance
“…This relationship between performance and activation reached significance in right dlPFC, left vlPFC, and bilateral premotor cortex. Remarkably, the same lateralization pattern was found in a previous study comparing performance subgroups of patients and controls (Tan et al, 2006) and is additionally supported by a meta-analysis indicating a strong performance-activation relationship in right dlPFC (Van Snellenberg et al, 2006). Previous studies indicate that this relationship is mediated by dopamine: while WM capacity correlated positively with dopamine synthesis in healthy subjects (Cools et al, 2008), the latter predicted dlPFC activation during WM in prodromal subjects (Fusar-Poli et al, 2010).…”
Section: Prefrontal Activation and Cognitive Performancesupporting
confidence: 84%
See 1 more Smart Citation
“…This relationship between performance and activation reached significance in right dlPFC, left vlPFC, and bilateral premotor cortex. Remarkably, the same lateralization pattern was found in a previous study comparing performance subgroups of patients and controls (Tan et al, 2006) and is additionally supported by a meta-analysis indicating a strong performance-activation relationship in right dlPFC (Van Snellenberg et al, 2006). Previous studies indicate that this relationship is mediated by dopamine: while WM capacity correlated positively with dopamine synthesis in healthy subjects (Cools et al, 2008), the latter predicted dlPFC activation during WM in prodromal subjects (Fusar-Poli et al, 2010).…”
Section: Prefrontal Activation and Cognitive Performancesupporting
confidence: 84%
“…Another meta-analysis demonstrated that this inconsistency primarily depends on task performance (Van Snellenberg et al, 2006). Hence, levels of dlPFC activation may reflect neural processing efficiency indicating individual differences of working memory capacity (Callicott et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such deficits in goal maintenance are found in the first-degree relatives of individuals with schizophrenia [56,57], as well as in individuals with schizotypal personality disorder [58,59]. Individuals with schizophrenia also show strong evidence of impairment on other tasks that may tap into goal maintenance, such as the Stroop task [e.g., 60] and the antisaccade task [e.g., 61], as do their first degree relatives [58] Individuals with schizophrenia also show consistent evidence of impaired prefrontal activity, particularly in dorsolateral regions, during tasks that require goal maintenance [e.g., 55,62,63]. Again, the first-degree relatives of individuals with schizophrenia also show evidence of impaired prefrontal activation during goal maintenance [57,64].…”
Section: Strong Evidence Of Impairment In Schizophreniamentioning
confidence: 99%
“…Without fully controlling for performance differences over the same dynamic range of WM load, it is difficult to know whether performance deficits in schizophrenia reflect primary dysfunction in task-related networks, suboptimal activation of these networks, and/or downstream effects of other disrupted networks (Van Snellenberg et al, 2006). Indeed, WM function depends not only on activation of dlPFC and other nodes within the frontoparietal control network (FPCN) but also on deactivation of the default mode network (DMN; Anticevic et al, 2010).…”
Section: Introductionmentioning
confidence: 99%